Imunoexpressão de efrina-B2 e Eph-B4 em adenoma pleomórfico carcinoma mucoepidermoide e carcinoma adenoide cístico glandulares salivares - Mendes, Jefferson Lucas (2025)
Salivary gland neoplasms represent a rare and heterogeneous group of tumors, with pleomorphic adenoma (AP), mucoepidermoid carcinoma (CME), and adenoid cystic carcinoma (CAC) standing out due to their prevalence, each presenting distinct histopathological characteristics and biological behaviors. Ephrins and their receptors have been evaluated and linked to tumor etiopathogenesis due to their role in modulating bidirectional intracellular signaling pathways involved in various cellular and tumoral phenomena—a field still scarcely explored in salivary gland neoplasms. In this context, the present study aimed to analyze the immunoexpression of ephrin-B2 and Eph-B4 proteins in AP, CME, and CAC samples, in relation to their histomorphological parameters. This was a histomorphological and immunohistochemical study employing polyclonal antibodies against ephrin-B2 and a monoclonal antibody against Eph-B4 in 15 AP, 15 CME, and 10 CAC cases from both major and minor salivary glands. Percentages of cytoplasmic and nuclear immunoexpression were assessed in five fields of highest immunoreactivity (400x magnification). Data analysis was performed using the Mann-Whitney and Kruskal-Wallis tests, followed by the Dwass-SteelCritchlow-Fligner multiple comparison post hoc test, and Spearman’s correlation test, considering a significance level of 5% (p < 0.05). The analyses demonstrated predominant cytoplasmic positivity for ephrin-B2 across the entire sample, with variation in expression levels among tumor types, particularly elevated in AP. Nuclear expression was absent in most cases. Although no statistically significant differences were found between tumor types (p = 0.875), a trend toward higher expression was observed in more aggressive groups, such as grade II/III CME (Md = 30.9) and the tubular/solid patterns in CAC (Md = 60.5). Eph-B4 was also cytoplasmically expressed in all samples (p = 0.084), with moderately higher levels in AP. A similar trend of increased expression was observed in more aggressive CME cases (Md = 24.8), while nuclear expression of this receptor was negative in the majority of the sample. No statistically significant correlation was found between ephrin-B2 and Eph-B4 expression in the evaluated tumors (p > 0.05). The findings suggest that the ephrin-B2/Eph-B4 axis, particularly in its cytoplasmic expression, may be functionally involved in modulating molecular events related to the pathogenesis of the evaluated salivary gland neoplasms—especially those associated with cell proliferation and viability in AP growth and molecular mechanisms underlying the malignant behavior of CME and CAC.